Dibenzocyclooctadiene Lignans from Schisandra chinensis with Anti-Inflammatory Effects - Rybnikář, Michal; Malaník, Milan; Šmejkal, Karel; Švajdlenka, Emil; Shpet, Polina; Babica, Pavel; Dall'Acqua, Stefano; Smištík, Ondřej; Jurček, Ondřej; Treml, Jakub (International journal of molecular sciences, 2024)
Schisandra chinensis (Schisandraceae) is a medicinal plant widely used in traditional Chinese medicine. Under the name Wu Wei Zi, it is used to treat many diseases, especially as a stimulant, adaptogen, and hepatoprotective. Dibenzocyclooctadiene lignans are the main compounds responsible for the effect of S. chinensis. As a part of ongoing studies to identify and evaluate anti-inflammatory natural compounds, we isolated a series of dibenzocyclooctadiene lignans and evaluated their biological activity. Furthermore, we isolated new sesquiterpene 7,7-dimethyl-11-methylidenespiro[5.5]undec-2-ene-3-carboxylic acid. Selected dibenzocyclooctadiene lignans were tested to assess their anti-inflammatory potential in LPS-stimulated monocytes by monitoring their anti-NF-κB activity, antioxidant activity in CAA assay, and their effect on gap junction intercellular communication in WB-ras cells. Some S. chinensis lignans showed antioxidant activity in CAA mode and affected the gap junction intercellular communication. The anti-inflammatory activity was proven for (-)-gomisin N, (+)-γ-schisandrin, rubrisandrin A, and (-)-gomisin J.
Keywords: Lignans; lignany; Schisandra; polycyklické sloučeniny; cyklooktany; Schisandra chinensis; lignan; gap junction; Cyclooctanes; Anti-Inflammatory Agents; Polycyclic Compounds; anti-inflammatory; antiflogistika; dibenzocyclooctadiene; antioxidant